The improvement of the production line of the assembly of audio product - Mohamad Saharrifudin Ishak (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The main reason for low production rate of audio baed products were inappropriate handling of assembly process. This study was conduted to reduce the product operating time. By using line-balancing process, this study will focus on the assembly process where cycle time of the product were investigted to increase the productivity. Based on observations, some of the cause of potential that could lead to a slowdown in production were identified.